(untitled) (REMUNOM, 2024)
An important milestone for the Brazilian construction industry was the creation of NBR 15575 in 2013, which establishes criteria for evaluating the performance of residential buildings. This standard addresses the identification and prevention of construction pathologies, such as infiltrations, cracks, and corrosion. NBR 15575 classifies and analyzes the causes of these failures, considering their impact on the durability, safety, and comfort of the building. Additionally, it provides guidelines for preventive and corrective maintenance practices to ensure the quality and longevity of constructions. This study adopts a pragmatic approach to inspect and analyze the pathological manifestations in buildings. The literature review highlights that building pathology, inspired by medicine, aims to understand and treat structural problems to prevent deterioration and ensure the integrity of structures over time. The technical inspection identified several pathological manifestations: mold and mildew, cracks and fissures, steel reinforcement corrosion, paint peeling, and mortar disaggregation. Mold and mildew were detected due to moisture resulting from roof problems and infiltration. The cracks and fissures, both vertical and horizontal, were attributed to structural movements and moisture. Steel reinforcement corrosion is a consequence of moisture penetration, while paint peeling was caused by application under humid conditions. Mortar disaggregation was caused by constant moisture and other factors.The diagnosis of these pathological manifestations indicates the need for building maintenance interventions, such as mortar replacement, wall reconstruction, and treatment of steel reinforcements to prevent corrosion. Such repairs are essential to ensure the safety, durability, and functionality of the building.